The co-occurrence of the SAVA syndemic, depression and anxiety as barriers to antiretroviral therapy adherence among sub-Saharan Africa population groups: A scoping review protocol. - Anton Delport; Hanani Tabana; Lucia Knight; Edwin Wouters (PLoS ONE)
Introduction The scale-up of access to antiretroviral therapy has transformed HIV from an acute, terminal disease to a manageable chronic illness. Yet, sustaining high levels of antiretroviral therapy adherence remain a challenge, especially in the sub-Saharan Africa region which is disproportionately affected by HIV. This protocol proposes a scoping review to explore literature reporting on the antiretroviral therapy adherence levels among people who experience substance abuse and violence (SAVA) syndemics, as well as mood disorders such as anxiety and depression among people living with HIV in sub-Saharan Africa. Methods and analysis This proposed scoping review will follow Arksey and O'Malley's methodological framework for conducting scoping reviews as refined by Levac et al. The review will follow the Joanna Briggs Institute's manual for conducting scoping reviews. Literature searches will be conducted using six databases: Academic search complete; APA PsycArticles; CINAHL; MEDLINE; SocINDEX and Web of science. Title screening will see the "Participant, Concept, Context" framework applied to identify relevant literature and will not include the appraisal of search results. Data charting will follow an adapted version of Trico and colleagues' PRISMA-ScR and results will be mapped descriptively and in tabular format. Furthermore, results will be discussed within the syndemics model of health, and summarised as a biosocial conceptual model. Ethics and dissemination The study will make use of secondary data that are readily available to the public and will not require ethical approval. We intend to publish our results in a peer-reviewed journal and disseminate our findings at relevant conferences and seminars.